Two Kinds of Weighted Biased Estimators in Stochastic Restricted Regression Model. (4th June 2014) - Liu, Chaolin; Jiang, Haina; Shi, Xinhui; Liu, Donglin
Abstract : We consider two kinds of weighted mixed almost unbiased estimators in a linear stochastic restricted regression model when the prior information and the sample information are not equally important. The superiorities of the two new estimators are discussed according to quadratic bias and variance matrix criteria. Under such criteria, we perform a real data example and a Monte Carlo study to illustrate theoretical results.